Molecular-scale thermoelectricity: as simple as 'ABC'. Issue 11 (19th October 2020) - Ismael, Ali; Al-Jobory, Alaa; Wang, Xintai; Alshehab, Abdullah; Almutlg, Ahmad; Alshammari, Majed; Grace, Iain; Benett, Troy L. R.; Wilkinson, Luke A.; Robinson, Benjamin J.; Long, Nicholas J.; Lambert, Colin
Abstract : If the Seebeck coefficient of single molecules or self-assembled monolayers could be predicted from measurements of their conductance–voltage ( G – V ) characteristics alone, then the difficult experimental task of measuring their thermoelectric properties could be avoided. Abstract : If the Seebeck coefficient of single molecules or self-assembled monolayers (SAMs) could be predicted from measurements of their conductance–voltage ( G – V ) characteristics alone, then the experimentally more difficult task of creating a set-up to measure their thermoelectric properties could be avoided. This article highlights a novel strategy for predicting an upper bound to the Seebeck coefficient of single molecules or SAMs, from measurements of their G – V characteristics. The theory begins by making a fit to measured G – V curves using three fitting parameters, denoted a, b, c . This 'ABC' theory then predicts a maximum value for the magnitude of the corresponding Seebeck coefficient. This is a useful material parameter, because if the predicted upper bound is large, then the material would warrant further investigation using a full Seebeck-measurement setup. On the other hand, if the upper bound is small, then the material would not be promising and this much more technically demanding set of measurements would be avoided. Histograms of predicted Seebeck coefficients are compared with histograms of measured Seebeck coefficients for six different SAMs, formed from anthracene-based molecules with different anchor groups and are shown to be in excellent agreement.